Efficacy and safety of Zi Gui Nv Zhen® capsules used in TCM for fertility preservation in patients with diminished ovarian reserve. (2nd January 2022) - Xu, Zhongting; Ruan, Xiangyan; Xu, Xin; Yang, Yu; Cheng, Jiaojiao; Luo, Suiyu; Min, Min; Li, Meng; Zhang, Luping; Ju, Rui; Jin, Fengyu; Mueck, Alfred Otto
Abstract: Objective: To evaluate for the first time whether Zi Gui Nv Zhen ® capsules (ZGNZC), until now used in traditional Chinese medicine (TCM) for menopausal complaints, can increase the fertility of Chinese women with diminished ovarian reserve (DOR). Methods: Prospective, randomized, open-labeled 3-monthly study; 109 DOR patients (aged 20–40 years) receiving either ZGNZC (experimental group, n  = 75) or not (control group, n  = 34). Main outcomes: markers for ovarian function, thickness/type of the endometrium during ovulation, and pregnancy rate. Between-group analysis (A) comparing experimental vs. control group and within-group analysis (B) comparing data at baseline and after study in each of both groups. Results: (A) Between-group-analysis: patients with ZGNZC had a higher endometrium thickness (0.75 vs. 0.62; p <.05) and higher anti-Müllerian hormone (AMH, 0.50 vs. 0.40; p <.05) than control group. Pregnancy rates were higher in the experimental than the control group (26.7% vs. 14.7%; n.s.). (B) Within-group-analysis: ZGNZC decreased levels of follicle-stimulating hormone (FSH, 11.42 vs. 8.69), increased estradiol-levels (E2, 56.09 vs. 73.36), and type A endometrium rates (5.3% vs. 39.7%) (all p < .05) and increased antral follicle count (AFC, 2 vs. 3). All hepato-renal biomarkers remained within the norm. The tolerability was good. There were no adverse events. Conclusions: In women with DOR who wish to conceive, three months' application of ZGNZC can improve ovarian function and oocyte quality by adjusting the neuroendocrine system, can improve endometrial properties and proliferation, necessary for a healthy pregnancy, and increased the clinical pregnancy rate in our prospective randomized observational study.